2014
DOI: 10.4067/s0718-95162014005000043
|View full text |Cite
|
Sign up to set email alerts
|

Biometric and biochemical attributes of alfalfa seedlings as indicators of stress induced by excessive cadmium

Abstract: The biometric and biochemical attributes of alfalfa (Medicago sativa L.) seedlings were studied after their exposure to 0-120 μM cadmium for 28 days using hydroponic culture. The growth, photosynthetic area and pigment contents (chlorophyll a, b and total) declined significantly (p ≤ 0.05) in the presence of high cadmium concentrations (90 and 120 μM). A steady increase in lipid peroxidation assessed via MDA production was observed with increasing levels of cadmium. Cadmium uptake by the plant tissues was conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Other studies also found a Cd-induced decrease in chlorophyll content in plants of Eucalyptus camaldulensis (MARQUES et al, 2011), Pisum sativum L. (JANUŠKAITIEN, 2012) and Medicago sativa L. (MAHMOOD et al, 2014).…”
Section: Resultsmentioning
confidence: 85%
“…Other studies also found a Cd-induced decrease in chlorophyll content in plants of Eucalyptus camaldulensis (MARQUES et al, 2011), Pisum sativum L. (JANUŠKAITIEN, 2012) and Medicago sativa L. (MAHMOOD et al, 2014).…”
Section: Resultsmentioning
confidence: 85%
“…However, the response was found nonsignificant at 600 and 900 µ M-CdCl 2 as compared to controls. The proline content was increased in Brassica juncea , Groenlandia densa , and Medicago sativa as the Cd concentration increased in the treatment [ 52 54 ]. Total chlorophyll content was decreased in the leaf of P. dactylifera plant under Cd stress in a dose dependent manner in relation to controls ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cd is a non-essential nutrient for growth of plants but in-spite of that reality it become accumulated in many crops via roots nutrients uptake channel. This high intake and accumulation of Cd reduced the photosynthesis activity and transpiration (Bazzaz et al, 1974;Mahmood et al, 2014). It also tremendously increases the respiration rate in many plants (Lamoreaux and Chaney, 1978;Lee et al, 1976).…”
Section: Introductionmentioning
confidence: 99%